FUNCTIONAL FOODS AS NATURAL THERAPEUTICS: A HOME SCIENCE PERSPECTIVE ON PREVENTIVE HEALTH - Ahirwar, Sangeeta (International Journal of Research -GRANTHAALAYAH, 2025)
Functional foods have emerged as a bridge between nutrition and medicine, offering physiological benefits beyond basic nourishment. This study explores the therapeutic potential of functional foods in preventive health care from a Home Science perspective, emphasizing their biochemical properties, mechanism of action, and potential role in reducing the risk of chronic diseases. A hypothetical comparative analysis was conducted on six selected functional foods—turmeric, flaxseeds, tomatoes, green tea, yogurt, and garlic—each containing distinct bioactive compounds such as curcumin, omega-3 fatty acids, lycopene, catechins, probiotics, and allicin. These compounds were analyzed based on their antioxidant capacity (µmol TE/g) and associated preventive health roles including anti-inflammatory, cardioprotective, and immunomodulatory effects. The findings suggest that functional foods play a significant role in mitigating oxidative stress, modulating gut microbiota, and enhancing metabolic homeostasis, thereby contributing to overall wellness. The study reinforces the concept that functional foods can serve as natural therapeutics when integrated into daily diets, aligning with global preventive health strategies and sustainable nutrition approaches.